2008
DOI: 10.1097/inf.0b013e31817b0799
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viral Infections in Children With Leukemia

Abstract: Respiratory viruses are found commonly during febrile episodes in children with leukemia. The detection of viruses permits the use of available antiviral agents, may explain a poor response to antimicrobial agents, and minimizes the proportion of febrile episodes without possible etiologic agents in children with leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
88
3
19

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 51 publications
7
88
3
19
Order By: Relevance
“…In addition, caspofungin has also been tried as salvage in patients with resistant fungal infections. Possibility that few of these pulmonary infiltrates might be due to viral infections cannot be ruled out [40]. Detailed virology work up was not done due to lack of facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, caspofungin has also been tried as salvage in patients with resistant fungal infections. Possibility that few of these pulmonary infiltrates might be due to viral infections cannot be ruled out [40]. Detailed virology work up was not done due to lack of facilities.…”
Section: Discussionmentioning
confidence: 99%
“…6 Using conventional and molecular techniques, respiratory syncytial virus (RSV), rhinovirus, parainfluenza and adenovirus have been the most frequently detected viruses in patients with cancer and fever ranging in frequency from 5% to 44%. 6,9,10 Arola et al 6 reported RVI in 37% of 75 febrile episodes occurring in 32 children with cancer using viral culture, antigen detection and serology. Implementation of gene amplification−based techniques has significantly improved our capacity to detect RVs in patients with cancer, including the detection of new and/or less common viruses such as bocaviruses, metapneumovirus, coronavirus and others, and occurrence of coinfections with >1 RV.…”
mentioning
confidence: 98%
“…Implementation of gene amplification−based techniques has significantly improved our capacity to detect RVs in patients with cancer, including the detection of new and/or less common viruses such as bocaviruses, metapneumovirus, coronavirus and others, and occurrence of coinfections with >1 RV. [9][10][11] For example, Koskenvuo et al 9 identified RVI in 44% of 138 febrile episodes occurring in children with leukemia by viral culture, antigen detection and polymerase chain reaction (PCR). In this series, rhinovirus (22%) followed by RSV (11%) were most common and 9% of episodes resulted positive for >1 virus.…”
mentioning
confidence: 98%
“…[1][2][3][4] This is strictly related to the demonstration or at least strong supposition that influenza can have a severe course or be complicated by superimposed bacterial infections in subjects with an underlying severe illness. [1][2][3][4] Children with neoplastic disease are included among those considered to be at risk because cancer and anti-cancer therapies impair immune function, thus making them more vulnerable to a variety of pathogens including influenza viruses, [5][6][7][8][9] which have a…”
Section: Introductionmentioning
confidence: 99%